Effect of feeding dried distillers' grains with solubles on milk yield and milk composition of cows in mid‐lactation and digestibility in sheep. Issue 2 (28th June 2013) - Westreicher‐Kristen, E.; Kaiser, R.; Steingass, H.; Rodehutscord, M.
Summary We evaluated the effect of three sources of dried distillers' grains with solubles (DDGS) in diets of mid‐lactating dairy cows on milk production and milk composition and on digestibility in sheep. DDGS from wheat, corn and barley (DDGS1), wheat and corn (DDGS2) and wheat (DDGS3) were studied and compared with a rapeseed meal (RSM). RSM and DDGS were characterized through in situ crude protein (CP) degradability. Nutrient digestibility was determined in sheep. Twenty‐four multiparous cows were used in a 4 × 4 Latin square design with 28‐day periods. Treatments included total mixed rations containing as primary protein sources RSM (control), DDGS1 (D1), DDGS2 (D2) or DDGS3 (D3). RSM contained less rapidly degradable CP (fraction a), more potentially degradable CP (fraction b) and more rumen undegradable CP (UDP) than the three DDGS. In vivo digestibility of RSM organic matter was similar to DDGS. Calculated net energy for lactation (NEL) was lower for RSM (7.4 MJ/kg DM) than for DDGS, which averaged 7.7 MJ/kg DM. Cows' dry matter intake did not differ between diets (21.7 kg/day). Cows fed D1 yielded more milk than those fed D3 (31.7 vs. 30.4 kg/day); no differences were found between control and DDGS diets (31.3 vs. 31.1 kg/day). Energy‐corrected milk was similar among diets (31.2 kg/day). Diets affected neither milk fat concentration (4.0%) nor milk fat yield (1.24 kg/day). Milk protein yield of control (1.12 kg/day) was significantly higher than D3 (1.06 kg/day) but not different form D1 and D2 (1.08 kg/day each). Feeding DDGS significantly increased milk lactose concentration (4.91%) in relation to control (4.81%). DDGS can be a suitable feed in relation to RSM and can be fed up to 4 kg dry matter per day in rations of dairy cows in mid‐lactation. However, high variation of protein and energy values of DDGS should be considered when included in diets of dairy cows.